Anti-diabetic effect of Daldinia eschscholtzii and Phomopsis mangiferae isolated from Bryophyllum pinnatum - Settu, Sugashini; Arunachalam, Sathiavelu (Bangladesh Journal of Pharmacology, 2023)
The aim of the present study was to isolate endophytic fungi and examine their anti-diabetic as well as antioxidant potential. Twenty-nine endophytic fungi were isolated from the stem and root parts of Bryophyllum pinnatum. Based on the presence of phytoconstituents, 16 endophytic isolates were tested for the inhibition of α-amylase enzyme and free radicals. Thirteen isolates showed significant inhibition of α-amylase enzyme (18.8 ± 0.8 to 62.5 ± 0.4%) and free radicals (15.3 ± 0.2 to 87.4 ± 0.8%). Good inhibitions were found in six isolates, which was further tested to validates its anti-diabetic activity by glucose uptake in yeast cell and glucose diffusion inhibition studies. The most active isolates were identified as Daldinia eschscholtzii (BPS17) and Phomopsis mangiferae (BPK9) by microscopic and molecular identification method. Identified fungal isolates were tested for glucose uptake using 3T3 cell lines (100 µg/mL) and the result showed effective glucose utilization. These finding provides evidence that D. eschscholtzii and P. mangiferae are potent endophytic fungi having anti-diabetic activity.